BURUNG SEBAGAI ATRAKSI EKOWISATA DI KAWASAN PARIWISATA UBUD, BALI - Dalem, A.A.G Raka; Widana, I N; Putri, I.A Trisna Eka (Bumi Lestari, 2016)
Research  on “Birds as an Ecotour Attraction in Ubud Tourist Resort, Bali” (Burung sebagai Atraksi Ekowisata di Kawasan Pariwisata Ubud, Bali) was undertaken in 2013. Aims of these research were as follows: first, to find out birds observed in Ubud Tourist Resort, Bali and second, to find out their potentials as ecotour attractions. Samples were collected by exploring the study sites and running interview between July and October, 2013.  Observation was carried out by using binoculars and number of individuals of birds was counted by using a counter when necessary.  Birds were identified such as through direct observation on the species, or through their calling.  Results of observation were compared with hand boooks, such as Mackinnon (1990) and Mackinnon et al. (1992). Birds data were recorded either on their species and on numbers (relative)/freqency, and the result was typed in tables.  The data provided such as the status (protected/not), migrant species or not, as well as their distribution.  In addition, locations where birds have been used as a tour attraction (ecotour attraction - bird watching), and how to set up their products were reported. From this research it can be concluded as follows.  In Ubud tourist resort at least 67 bird species have been identified, in which 7 (seven) were birds that were restricted their distribution in Indonesia, namely:  Halcyon cyanoventris, Alcedo caerulescens, Padda oryzivora, Prinia familiaris, Treron griseicauda, Dicaeum trochileum, and Gallus varius. In addition, from this reserach it was observed seven species of migrating birds: Hirundo rustica, Merops philippinus or M. superciliosus, Accipiter soloensis, Actitis hypoleucos, Tringa glareola, Gallinago stenura, and Apus pacificus. From all birds observed, there were 14 species that were classified as protected species in Indonesia, namely: Sturnus melanopterus, Anhinga melanogaster, Bubulcus ibis, Egretta alba, Egretta garzatta, Egretta intermedia, Halcyon cyanoventris, Halcyon chloris, Alcedo caerulescens, Haliastur indus, Nectarinia jugularis, Anthreptes malacensis, Rhidipura javanica, and Accipiter soloensis. Based on data from survey and interview, it was revealed that seven trekking routes were identified in which birds were utilised as ecotour attractions or the routes of which have a potential to be developed as ecotour attractions (where birds utilised as their tourist attractions in Ubud tourist resort and ajacent areas), such as: (1) Subak Sok Wayah Ubud and its surrounding areas; (2) Melinggih - Subak Kembang Kuning and their surrounding areas; (3) Laplapan, Banjar Sala and their surrounding areas; (4) Kliki (Bangkiang Sidem) and its surrounding areas; (5) Tirta Temple Mas Village and its surrounding areas; (6) Banjar Pande Peliatan Village - Alas Arum temple and their surrounding areas; (7) Petulu and its surrounding areas. Community perceptions on bird conservation and bird based ecotoursim in Ubud tourist resort showed that: in general the community believed the need for conservation of birds,and they said that the development of bird based ecotour activities have given benefit for the community, such as providing jobs and source of income for them, even though some constraints still need to be overcome, such as trekking trails that have not been perfect, the smell of feces of birds, and weekness in human resources capability. From statements of stakeholders (community, govenment, industry, and visitors), it can be revealed that the commitment of all is needed in bird conservation, because they become important part of nature, in the sustainability of nature or ecosystem. The media for meeting and discussing for development of birds based tourism activities especially bird watching in Ubud tourist resort need to be improved. Limitation in time may caused incompleteness of the bird data collected on this research. As a result, a longer time in research is recommended. In addition, other studies or research are also needed to get more data, the data of whcih their availability are still very limited.  For example, research on bird habitats are also need to be undertaken.
Keywords: birds, bird watching, Ubud tourist resort, Bali, trekking